A rare case of folliculotropic mycosis fungoides with eosinophilic pneumonia - Yuma Hanaoka; Eiji Kiyohara; Mamori Tani; Shinsuke Kusakabe; Tetsuo Maeda; Atsushi Tanemura; Manabu Fujimoto (Frontiers Media S.A., 2022)
We describe the first case of folliculotropic mycosis fungoides (FMF) involving eosinophilic pneumonia (EP). It would be difficult to treat EP without CTCL treatment.